Pengaruh penggunaan model problem based learning (PBL) berbantuan handout terhadap kompetensi fisika siswa kelas X MIPA SMAN 2 kota Solok - Rahmat Trio Hidayat; Yurnetti Yurnetti; Hamdi Hamdi (Universitas Negeri Padang, 2019)
Learning outcomes in students Physics subject is not as expected, because students' mastery of Physics material is still lacking. Besides that the learning model used is still not varied and teaching materials have not been fully used. Therefore, researchers used the Handout-Based Problem Based Learning (PBL) learning model. This study aims to determine the effect of the use of a Problem Based Learning (PBL) Assisted Handout Model on the Physics Competence of Students in Class X MIPA SMAN 2 Kota Solok. This type of research is a quasi-experimental research design with a randomized control group only design. The study population was all students of class X MIPA SMAN 2 Solok City registered in 2018/2019. The research sample was taken using purposive sampling technique. Research data is student learning outcome data on attitude competency, knowledge competency, and skill competency. The research instrument used was an observation sheet to measure attitude competency, a final test to measure knowledge competence, and a performance assessment sheet to measure competency skills. The research data were analyzed by two average similarity tests. The average similarity test of two is conducted for the value of learning outcomes of each knowledge competency and skills competency. As for attitude competency using data description results from each meeting.The results showed the average physics learning outcomes in both sample classes 80.40 and 75.10 for knowledge competence, 83.53 and 82.75 for skills competency from the t test, obtained tcount> ttable so that alternative hypotheses were accepted for knowledge competence, while for the competency skills of the t test, obtained tcount>ttable so that the alternative hypothesis is accepted. The conclusion of the research is the hypothesis which states that there is a significant influence on the use of a problem based learning model assisted by a handout on the physics competence of students in class X MIPA SMAN 2 Kota Solok.